PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, AKTIVITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013-2016 - Siti Kusmawati; Ronny Malavia Mardani (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The purpose of this study is to test the effect of profitability ratios, liquidity, activity on stock returns listed on the Stock Exchange (BEI) 2013-2014.This sampling technique using purposive sampling, based on the analysis results can be concluded that the test result F of 17,850 with a significant level of 0,000 < 0,05 which mean that there is at least one independentvvariable that has the ability to explain independent variables. Keyword : Profitability, Liquidity, Activity, and Stocks return